Quality of Prenatal-care Utilization in Bangladesh: Socioeconomic Factors: Quality of Prenatal-care Utilization in Bangladesh - Khan, Rana Ejaz Ali; Noreen, Sara (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
The delivery of prenatal-care services and its quality reduces mortality and morbidity in mothers and neonates. The current study has attempted to explore the socioeconomic determinants of quality of prenatal-care utilization in Bangladesh. Micro-data set comprising 22437 observations has been taken from Bangladesh Demographic Health Survey (BDHS) 2004 and 2007. Ordered logistic regression is applied to estimate the correlation between quality of prenatal-care utilization and explanatory variables. The quality of prenatal-care utilization is measured by simple additive index by taking six components of prenatal-care. The results have revealed that the woman’s current age improves the probability of quality of prenatal-care utilization while age square decreases it. The number of died children and ratio of male to female children of a woman negatively influences the likelihood of quality of prenatal-care utilization. Age of the woman at first marriage, education of woman and her partner, household’s wealth status and urban locality of the household and large/capital city raise the probability of quality of prenatal-care utilization. The results about administrative divisions of Bangladesh have revealed statistically insignificant impact on quality of prenatal-care utilization which demonstrates that there exists no disparity among these divisions in the perspective of use of quality prenatal-care services by women.